Lung function, respiratory illness, and passive smoking in British primary school children. - Rona, R J (1993)
BACKGROUND: Many studies have reported a significant association between parents' smoking and reduced lung function in their children, but often the association has been found to be significant only in relation to maternal smoking. There have been few epidemiological studies on this topic in Britain. METHODS: Spirometry, in 2756 children aged 6.50-11.99 years, was carried out in a representative sample of English children, an inner city and ethnic minority sample, and a Scottish sample. Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and forced expiratory flow rates of 25-75% and 75-85% (FEF25-75 and FEF75-85) were measured and standardised scores obtained separately for the English representative sample, the Scottish sample and subgroups in the inner city sample, white and Afro-Caribbean children and those originating from the Indian subcontinent. Multiple regression analyses were used to assess associations of FVC, FEV1, FEF25-75 and FEF75-85 with the passive smoking and respiratory illness, with adjustment for a large number of potential confounders. Passive smoking was defined in terms of reported number of cigarettes smoked at home by each parent. The respiratory symptoms and illnesses assessed were wheeze, asthma and bronchitis attacks, cough in the morning, and cough at any other time as reported by parents. RESULTS: Maternal smoking, but not paternal smoking, was associated with reduced FEF25-75 and FEF75-85 in boys. No association was found between passive smoking and lung function in girls, but in an analysis including both sexes the interaction of sex and parental smoking on lung function was not significant. With few exceptions, FEV1, FEF25-75 and FEF75-85 were reduced in children with wheeze and asthma attacks. CONCLUSIONS: The effect of passive smoking may depend on the close contact of a parent with a susceptible child as only maternal smoking in boys was significantly associated with impaired lung function. However, this explanation remains unsubstantiated. A parent's report of wheeze and asthma attacks in the child is reflected in reduced lung function.